Detection of Lyme disease spirochetes and Borrelia miyamotoi in samples of Czech patients - Kapurani, Helena (Jihočeská univerzita, 2022)
Lyme borreliosis is a disease caused by infection of selected members of the Borrelia burgdorferi sensu lato complex, a genus that keeps growing. With time, more and more members of this complex were identified as pathogenic for humans. This work aims to detect the spectrum of Borrelia spirochetes present in samples of Czech patients diagnosed with Lyme disease. Analysis will be used to suggest a tendency between the presence of the spirochetes' DNA found and the diagnosis of the patients.
Detection of Lyme disease spirochetes and Borrelia miyamotoi in samples of Czech patients
Keywords: Lyme borreliosis; B. burgdorferi; B. miyamotoi; infection; Czech Republic; patients; Lyme borreliosis; B. burgdorferi; B. miyamotoi; infection; Czech Republic; patients